Design of integrated fire alarm system for integrated pipe gallery based on multi-environmental sensors. (28th September 2020) - Wei, Liming; Guo, Xing; Wang, Qiucui
This paper describes the design of a fire warning system for the purpose of preventing accidents such as fires in integrated pipe gallery. The sensor is used to monitor the internal environmental parameters of the pipe gallery, and the combination of Programmable Logic Controller (PLC) and Laboratory Virtual Instrument Engineering Workbench (Labview) software is used to design the overall scheme of the system. The upper computer interface and the system operation framework are given, and the selection process of the lower computer and the simulation process of the upper computer are explained. The system can prevent to some extent the early stage of the fire. Earlier control of the fire hazard in the pipe gallery from the source can provide a guarantee for the safe operation of the integrated pipe gallery.